1976
DOI: 10.1099/00221287-96-1-25
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Alkalinity and Hypertonicity on the Morphology and Motility of Leptospira interrogans (biflexa) strain B16

Abstract: S U M M A R YEffects of alkalinity and hypertonicity on the motile behaviour of Leptospira interrogans (bzflexa) B I 6 were observed, quantified, and compared with effects previously shown by similar factors on the motility of eubacteria. Leptospira interrogans tolerated relatively high concentrations of hydroxide ions. Motility similar to that in controls was observed at pH values up to 9-8; but at pH 10.0 motility declined sharply with time of exposure, and there was structural alteration, visible as a blebb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1979
1979
2013
2013

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…It is possible that spirochetes are resistant to rifampin because this antibiotic cannot penetrate the outer sheath that envelops the spirochetal cell. The function of the outer sheath in spirochetes is largely unknown, but it has been suggested that it may act as a permeability barrier (2,12).…”
Section: Downloaded Frommentioning
confidence: 99%
“…It is possible that spirochetes are resistant to rifampin because this antibiotic cannot penetrate the outer sheath that envelops the spirochetal cell. The function of the outer sheath in spirochetes is largely unknown, but it has been suggested that it may act as a permeability barrier (2,12).…”
Section: Downloaded Frommentioning
confidence: 99%
“…Therefore, the motility of Leptospira is thought to play a critical role in invasion of animals or migration within them. However, L. biflexa cells are reportedly immobilized by hypertonic solutions, for example, 0.5 and 1.0 M sucrose solutions . As mentioned above, pathogenic Leptospira cells are excreted in the urine .…”
mentioning
confidence: 99%
“…Thirdly, among animal cells, the kidney cells well regulate intracellular osmolality and pH suitable for leptospire survival, and thus are important target (13,14).…”
Section: Kidney As a Tropism Organ For Leptospiresmentioning
confidence: 99%